Reduced Emissions for Deforestation and Degradation: A Critical Review - Hufty, Marc; Haakenstad, Annie (Consilience, 2011)
“Reduced emissions from deforestation and forest degradation” (REDD) is emerging as a major new climate change mechanism that could deeply impact the financial, social and institutional dynamics of deforestation, conservation, and development in many developing countries. It has the potential to influence global forest governance in a socially acceptable way. The mechanism as it stands needs much improvement to avoid the pitfalls of earlier forest governance mechanisms. The research, at this stage, is not sufficient to improve it. Most of the literature is fairly slanted towards technical issues and the prospective design of the scheme or normative opposition to it. Despite this copious amounts of scholarly and advocacy work, there is too little attention focused on the social and governance dimensions of the proposals.